Open flow microperfusion: pharmacokinetics of human insulin and insulin detemir in the interstitial fluid of subcutaneous adipose tissue. Issue 2 (26th October 2014) - Höfferer, C.; Tutkur, D.; Fledelius, C.; Brand, C. L.; Alsted, T. J.; Damgaard, J.; Nishimura, E.; Jeppesen, C.B.; Mautner, S. I.; Pieber, T. R.; Sinner, F.
<x xml:space="preserve">Abstract</x> Aims To compare the time profile of insulin detemir and human insulin concentrations in the interstitial fluid (ISF) of subcutaneous adipose tissue during constant i.v. infusion and to investigate the relationship between the pharmacokinetics of both insulin molecules in plasma and the ISF of subcutaneous adipose tissue. Methods During a 6‐h hyperinsulinaemic–euglycaemic clamp (plasma glucose level 8 mmol/l) human insulin (21 and 42 pmol/min/kg) or insulin detemir (209 and 417 pmol/min/kg) were infused i.v. in eight rats per dose level. Open flow microperfusion (OFM) was used to continuously assess interstitial insulin concentrations in subcutaneous adipose tissue. Results At the lower infusion rate, insulin detemir appeared significantly later in the ISF than in the plasma (p < 0.05) and also appeared later in the ISF relative to human insulin (p < 0.005). Conclusions By using OFM we were able to monitor albumin‐bound insulin detemir directly in the ISF of subcutaneous tissue and confirm its delayed transendothelial passage to a peripheral site of action.